Development of Parijoto EthnoVlog Media to Explain the Scientific Reconstruction and Explanation of Parijoto (Medinilla javanensis) as Body Immunity - Indah Beti Lestari; Sudarmin Sudarmin; Ellianawati Ellianawati; Woro Sumarni; Helina Pancawardhani (International Conference on Science, Education, and Technology, 2021)
This research is a research and development of the ADDIE model to implement and evaluate the EthnoVlog learning media, namely at the Design and Development stage. This study aims to explain the scientific reconstruction and explanation of Parijoto (Medinilla javanensis) as body immunity. This research is located on the slopes of the Muria Mountains, Colo Village, Dawe District, Kudus Regency, with the research subject of Parijoto farmers. Data collection techniques were carried out by observation, interviews with selected sources, and validation by experts. Data analysis and scientific reconstruction refer to Sudarmin et al. (2020), consisting of four steps: verification, reduction, validation, and conceptualization. The scientific reconstruction and explanation of Parijoto (Medinilla javanensis) show Parijoto contains flavonoid compounds, tannins, saponins, alkaloids, and antioxidants that the body needs for the body's immune system. The literature-based scientific reconstruction and explanation results are used as a database to design engaging Parijoto EthnoVlog learning media. Based on data analysis, it can be concluded that the Parijoto EthnoVlog media is feasible to be applied directly in science learning as an alternative media during the Covid-19 pandemic.